Pengembangan ekowisata melalui peningkatan kemampuan fasilitator outbound di Desa Cihaur Kecamatan Maja Kabupaten Majalengka - Pajar Anugrah Prasetio; Febby Fajar Nugraha; Gilang Kripsiyadi Praramdana (Abdimas Siliwangi, 2023)
Ecotourism development through increasing the ability of outbound facilitators is to provide education in improving welfare around ecotourism areas, increasing community productivity in order to form independent villages, and increasing village original income (PAD) through the ecotourism sector. Community Service Activities (PKM) are carried out using an outdoor activity approach, including: (1) Lecture Method, (2) Question and Answer Method, (3) Field Introduction, (4) Field practice and mentoring, and (5) Reflection. The results of Ecotourism Development Through Improving the Capability of Outbound Facilitators in Cihaur Village, Maja District, Majalengka Regency, namely: (1) The insight, knowledge, experience and motivation of outbound facilitators at tourist attractions in developing ecotourism in Cihaur village is increasing. (2) Provide a significant impact on welfare around ecotourism areas, increase community productivity in forming independent villages, and increase village original income (PAD) through the Cihaur Village Pine Forest ecotourism sector